The Impact of Plant-Based Diet on Menstrual Cycle Irregularities in Women with Polycystic Ovary Syndrome (PCOS) at Wasit City - Naser, Lina Mannam (American Journal of Biomedicine and Pharmacy, 2025)
Polycystic Ovary Syndrome (PCOS) is a common endocrine-metabolic disorder characterized by hormonal imbalances, ovulatory dysfunction, and menstrual irregularities. While pharmacological treatments exist, dietary strategies offer a non-invasive alternative for managing PCOS symptoms. This randomized controlled trial evaluated the impact of a plant-based diet on menstrual cycle frequency, hormonal parameters, and ovulatory function in women with PCOS in Wasit city. Fifty women with irregular menstrual cycles were randomly assigned to a plant-based diet group (n=25) or a control group (n=25) for a three-month intervention period. The plant-based group received structured dietary counseling emphasizing whole, minimally processed plant foods, while the control group maintained their habitual diet. Primary and secondary outcomes included menstrual cycle frequency, serum hormone levels (testosterone, LH/FSH ratio), fasting insulin, and mid-luteal progesterone. Post-intervention comparisons revealed significantly improved outcomes in the plant-based group. Menstrual cycle frequency was higher (0.98 vs. 0.61 cycles/month, p<0.001), LH/FSH ratio was lower (1.52 vs. 2.25, p<0.001), and fasting insulin levels were reduced (13.8 vs. 16.2 μIU/mL, p=0.03). Mid-luteal progesterone levels, indicating ovulation, were markedly elevated (7.17 vs. 3.15 ng/mL, p<0.001). Multiple linear regression confirmed that diet group, mid-luteal progesterone, and LH/FSH ratio significantly predicted menstrual frequency (R²=0.64, p<0.001). Logistic regression identified plant-based diet as the sole significant predictor of ovulation (OR ≈ 293.3, p=0.001), independent of other hormonal or metabolic parameters. These findings suggest that a fully plant-based diet may significantly improve reproductive outcomes in PCOS by restoring menstrual regularity and enhancing ovulation, potentially through pathways beyond traditional endocrine markers. This study fills a critical gap by evaluating a holistic plant-based approach and highlights its potential as a lifestyle-based intervention in PCOS management.